Analysis of quadríceps thickness and handgrip strength in hospitalized individuals: A cross-sectional study (Research, Society and Development, 2025)
Population aging and the increase in non-communicable chronic diseases have contributed to the occurrence of sarcopenia. This loss of muscle mass and strength is associated with worse clinical outcomes, such as functional disability, prolonged hospitalization, and higher mortality. The objective was to analyze and compare quadriceps muscle thickness and handgrip strength in hospitalized individuals with different chronic diseases. It is an observational, cross-sectional study conducted between August and December 2025, including 14 participants divided into two groups: chronic (n=7) and control (n=7). Quadriceps thickness was assessed by ultrasound (B-mode), and handgrip strength was measured using an electronic dynamometer. Data were analyzed using SPSS 25.0, applying Student’s t-test, Mann–Whitney test, chi-square test, and Fisher’s exact test, with p